2022
DOI: 10.3390/en15186669
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Different Types of Automated Vehicles on Traffic Flow Characteristics and Emissions: A Microscopic Traffic Simulation of Different Freeway Segments

Abstract: Different types of automated vehicles (AVs) have emerged promptly in recent years, each of which might have different potential impacts on traffic flow and emissions. In this paper, the impacts of autonomous automated vehicles (AAVs) and cooperative automated vehicles (CAVs) on capacity, average traffic speed, average travel time per vehicle, and average delay per vehicle, as well as traffic emissions such as carbon dioxide (CO2), nitrogen oxides (NOx), and particulate matter (PM10) have been investigated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In the literature, different driving behaviours of AVs have been assumed; for example, they can be grouped as cautious and aggressive [7,50,51] based on the levels of automation, where level 5 represents the most aggressive AVs. AVs can be further clustered as cooperative/connected AVs (CAVs) and autonomous (without communication capability) AVs (AAVs) [12,11]. What is more, the types of roadway have a significant impact on the driving characteristics of AVs, as the study [22], for example, showed that vehicles are more conservative on basic freeways than on merging and diverging freeway segments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, different driving behaviours of AVs have been assumed; for example, they can be grouped as cautious and aggressive [7,50,51] based on the levels of automation, where level 5 represents the most aggressive AVs. AVs can be further clustered as cooperative/connected AVs (CAVs) and autonomous (without communication capability) AVs (AAVs) [12,11]. What is more, the types of roadway have a significant impact on the driving characteristics of AVs, as the study [22], for example, showed that vehicles are more conservative on basic freeways than on merging and diverging freeway segments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the literature, two primary streams of studies use Vissim to replicate the driving behaviours of AVs using either internal or external modelling techniques. e first stream (e.g., see [7,12,25,32]) uses the internal modelling, and modifies the default Wiedemann driving logic (car-following) and lane-changing parameters to simulate the desired driving behaviours. e second stream, which uses the external Vissim interfaces and the external modelling methodology, sends user-defined algorithms to a dynamic link library to imitate the driving logic of AVs (e.g., see [33,34]).…”
Section: Methodological Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…It is expected that the proportion of AVs would gradually increase in the near future, which initially coexist with conventional vehicles (CVs) under mixed traffic condition [1][2][3][4]. Although there are still many unanswered questions regarding the precise effects of AVs on energy and the environment, it is generally acknowledged that at increasing AV penetration, a substantial net decrease in greenhouse gas emissions can be achieved [5][6][7][8]. e heterogeneous blend of AVs and CVs will undoubtedly have a substantial impact on traffic performance.…”
Section: Introductionmentioning
confidence: 99%